Pembelajaran Al-Qur’an Era Covid-19: Tinjauan Metode dan Tujuannya pada Masyarakat di Kutacane Aceh Tenggara - Rahmat Rifai Lubis; Nana Mahrani; Darwis Margolang; Muhammad Shaleh Assingkily (Universitas Islam Lamongan, 2020)
Al-Qur'an is sustainable until the Day of Resurrection, as well as learning the Qur'an must be endeavored to sustainably be given to mankind regardless of the circumstances, including the Covid-19 pandemic situation. This paper aims to analyze the learning of the Qur'an in the Covid-19 era in Kutacane, Aceh Tenggara. The formulation of this study focuses on discussing how the learning method of the Qur'an in the Covid-19 era in Kutacane, Southeast Aceh, the objectives of learning the Koran are still prioritized in the Covid-19 era and the learning objectives of the Qur'an are given to anyone. . For this reason, data collection was carried out qualitatively by using the field study method. The results of this study indicate that (1) the method of learning al-Qur'an is carried out using the halaqah system and learning at the home of a teacher; (2) the purpose of this lesson is that the children will love the Qur'an since childhood and bring the Qur'an to life in the Covid-19 era; and (3) learning targets are given to primary age children in Darussalam Village, Kutacane Aceh Tenggara.